FEASIBILITY ANALYSIS OF AGRIBUSINESS FOR OYSTER MUSHROOM COMMODITIES (CASE STUDY: KUMBUNG JAMUR JAWARA, BOGOR AREA) - Habibi, Muhammad Yunus; Sumiasih, Inanpi Hidayati; Arman, . (Universitas Trilogi, 2025)
This study provides an overview of the business prospects to support strategic decision-making in the development of oyster mushroom cultivation at Kumbung Jamur Jawara. The objective is to assess the feasibility and sustainability potential of the oyster mushroom farming business at Kumbung Jamur Jawara. The research was conducted from May to July 2024 at Jl. Raya Sukajaya, Desa Sukajaya, Tamansari District, Bogor Regency, West Java, using a quantitative and qualitative research approach. Data used includes both primary and secondary data. Data analysis evaluates the feasibility of the oyster mushroom agribusiness from human resource aspects, including management levels, job descriptions, and work simulations at Kumbung Jamur Jawara; technical aspects, covering raw materials and production; and financial aspects, using R/C Ratio and Break-Even Point (BEP) calculations. Results indicate that this business is feasible, with an R/C Ratio of over 1, specifically 1.37, indicating revenue is sufficiently high compared to operational costs. BEP analysis shows that the breakeven point is reached at a production level of around 1,169 kg, with a minimum price of Rp 8,038. Thus, oyster mushroom cultivation at Kumbung Jamur Jawara is theoretically expected to exceed the breakeven point.